Opioid crisis at the Jersey Shore—special report. (31st August 2017) - Dudley, Larissa S; Konomos, Dorothy; Robbins, Vince; Qiu, Linda; Bauter, Robert; Merlin, Mark A
Abstract: The USA is experiencing an epidemic of drug overdoses and deaths with a 200% increase in overdose deaths involving opioids including heroin. Legislation since 2013 has created paths to reduce opioid overdose deaths and since, basic life support (BLS) and police agencies have been administering naloxone to patients with suspected opioid overdoses as part of standard treatment protocols. Charts were reviewed from 1 January 2016 to 15 April 2016 on the de-identified electronic medical records of patients in a two-county system comprising the 'Jersey Shore' who received naloxone to determine the number of naloxone administrations and heroin overdoses. Additionally, narratives were examined for evidence of heroin use. Of the 312 patients, 213 received a first dose of naloxone by a family member or bystander, police, or by BLS; 99 received a first dose by a paramedic (ALS). About 233 were initially unresponsive or had altered mental status that improved after naloxone administration. About210 (67.3%) charts illustrated obvious opioid use. Of the note, 282 patients arrived to an emergency department alive. About 30 patients were pronounced dead. From 1 February 2016 to 31 March 2016, the number of opioid overdoses increased and the subsequent use of naloxone has increased by 176%.